2003
DOI: 10.1002/pros.10182
|View full text |Cite
|
Sign up to set email alerts
|

Lesions missed on prostate biopsies in cases sent in for consultation

Abstract: Although the number of prostate biopsies with missed lesions in a consult-based population of prostate biopsies appears relatively high (2.7%), the detection of the missed lesions would have only effected a definite change in care in 0.5% of all patients or a possible change in care in another 0.5% of patients. Our data underestimates missed lesions, as the entire specimen was not submitted for review in 41% of cases. Although our incidence of missed lesions gives some indication as to the magnitude of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…Kronz et al. 10 studied 3251 biopsy cases seen in consultation, and identified 87 (2.7%) patients with missed lesions, including HGPIN, of whom 32 (1%) had prostatic adenocarcinoma. This figure is probably an underestimate, as only selected biopsies were submitted for consultation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kronz et al. 10 studied 3251 biopsy cases seen in consultation, and identified 87 (2.7%) patients with missed lesions, including HGPIN, of whom 32 (1%) had prostatic adenocarcinoma. This figure is probably an underestimate, as only selected biopsies were submitted for consultation.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously published a single-year audit, which used the definition of those cases changed from benign to cancer, and this showed a false-negative error rate of 0.6%, 16 but this larger audit used a broader definition, and as a result found a higher rate of 1.7%. Kronz et al 10 studied 3251 biopsy cases seen in consultation, and identified 87 (2.7%) patients with missed lesions, including HGPIN, of whom 32 (1%) had prostatic adenocarcinoma. This figure is probably an underestimate, as only selected biopsies were submitted for consultation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although detection of the disease is possible at an early stage using either serum prostate specific antigen measurements or biopsies, screening has not been shown to improve survival. 4 Conventional treatments for earlystage disease involve watchful waiting, radiotherapy, and prostatectomy, depending on patient age and comorbidities. In the case of metastatic prostate cancer, androgen suppression remains the treatment of choice after more than 50 years.…”
mentioning
confidence: 99%
“…Kronz et al . studied 3251 biopsy cases seen in consultation and identified 87 (2.7%) patients with missed lesions, of which 32 (1%) had prostatic adenocarcinoma 2 . These errors would have changed patient management in 0.5% of all the patients.…”
mentioning
confidence: 99%